Quartet Cards Game as a Media Used to Promote Students Vocabulary Mastery - Meidy, Rina Septria; Zaitun, Zaitun (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This research had the objective of measuring whether or not Quartet cards game used as attractive media effective to promote 7th grade students' vocabulary mastery. This quantitative research applied experimental approach with one group pre-test and post-test design. There were 28 students of 7th grade, registered in even semester of academic year 2022/2023, participated as sample in this study. The tools used in collecting the data were validated pre-test and post-test of vocabulary knowledge. In analyzing the data, paired-sample test was used to determine the correlations between variables and to decide which hypothesis was accepted. Initial data calculation revealed that in the average, the students reached higher achievement in the post test than in the pre-test in which the mean score gained in the post-test was 77.71 while in the pre-test was 55.96 which meant that vocabulary mastery of the students was 21.95 points increased after they were taught by using Quartet cards game. Besides, the statistical analysis indicated that the correlation coefficient between two variables was 0.678 with the sig value of 0.001 or < than a probability of 0.05, this confirmed that there was a relationship between pre-test and post-test variables. The computation of paired-sample test revealed that Sig. (one-sided and two-sided p) was <0.001 which showed that there was different achievement reached by the students after Quartet cards game was used in the learning. Based on these findings, this research concluded that Quartet cards game promoted 7th graders’ vocabulary mastery. Thus, this study accepted Ha and rejected H0. Keywords: teaching aids, learning media, quartet cards game, vocabulary mastery Abstrak Penelitian ini memiliki tujuan untuk mengukur apakah Quartet cards game yang digunakan sebagai media yang atraktif efektif dalam meningkatkan penguasaan kosakata siswa kelas 7. Penelitian kuantitatif ini menerapkan pendekatan eksperimen dengan disain ‘one group pre-test post-test’. Sejumlah 28 siswa kelas 7 MTs Darussalam, Tangerang Selatan, terdaftar pada semester genap tahun ajaran 2022/2023, berpartisipasi sebagai sampel dalam penelitian ini. Alat yang digunakan dalam mengumpulkan data adalah uji pengetahuan kosa kata sebelum dan sesudah (pre-test dan post-test) yang telah divalidasi. Dalam menganalisis data, paired sample test digunakan untuk menentukan korelasi antar variabel dan untuk menentukan hipotesis mana yang diterima. Kalkulasi data diawal menunjukkan bahwa secara rerata, siswa mencapai hasil yang lebih tinggi pada post-test dibandingkan capaian mereka di pre-test, dimana nilai rerata di post-test adalah 77.71 sedangkan pada pre-test adalah 55.96 dimana hal ini menunjukkan bahwa penguasaan kosa kata siswa meningkat sebesar 21.95 poin setelah mereka diajarkan dengan menggunakan media Quartet cards game. Selain itu, analisis statistika menunjukkan korelasi koefisien antar variabel adalah 0.678 dengan nilai signifikan 0.001 atau lebih kecil (<) dari kemungkinan 0.05, dan hal ini mengkonfirmasi bahwa terdapat korelasi antara variabel pre-test dan post-test. Perhitungan dari paired-sample test menunjukkan bahwa Signifikan (one-sided dab two-sided p) lebih kecil dari 0.001 (<0.001) yang menunjukkan bahwa terdapat perbedaan capaian yang diraih oleh siswa setelah Quartet cards game digunakan dalam pembelajaran. Berdasarkan temuan ini maka disimpulkan bahwa Quartet cards game meningkatkan penguasaan kosa kata siswa kelas 7. Dengan demikian, ma.ka penelitian ini menerima Ha dan menolak H0.